Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Find x , (- 1/3) ^ (x - 2) ÷ (1/3) ^ - 3 = (1/3) ^ (2x + 7)​

Sagot :

Answer:

x = -6.

Step-by-step explanation:

(- 1/3) ^ (x - 2) ÷ (1/3) ^ - 3 = (1/3) ^ (2x + 7)​

(- 1/3) ^ (x - 2)  = (1/3) ^ (2x + 7) * (1/3) ^ - 3

(- 1/3) ^ (x - 2)  = (1/3) ^ (2x + 7 - 3)

(- 1/3) ^ (x - 2)  = (1/3) ^ (2x + 4)

(1/3)^(x - 2) = (1/3)^(2x + 4)

x - 2 = 2x + 4

x = -6.